Pemberian Edukasi Mindfullness untuk Menurunkan Stres Belajar Remaja pada Siswa Kelas X SMAN 3 Bone - Musdalipa Musdalipa; Ria Rizka Mansur (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Adolescence is a crucial developmental phase marked by physical, emotional, and social changes, alongside new challenges brought about by the digital age. These changes often contribute to heightened stress and anxiety, particularly in academic settings. School, with its rigorous demands and social pressures, serves as a significant stressor. This community service project aimed to enhance the knowledge and practice of mindfulness among 10th-grade students at SMAN 3 Bone, specifically focusing on helping them cope with psychological and social pressures. Conducted on August 22, 2025, the project involved 33 female students navigating the transitional period of adolescence. The intervention consisted of an initial survey to assess baseline knowledge, followed by educational sessions on mindfulness theory and practical exercises, as well as group discussions and reflections. The results demonstrated a significant increase in students' mindfulness knowledge and skills, with the final average score reaching 80. Evaluation was based on observations throughout the activity and post-intervention assessments. The outcomes suggest that mindfulness education is an effective strategy for improving students’ ability to manage stress and anxiety. Despite the positive impact, challenges related to the implementation of mindfulness education within the school setting were identified, including the need for more structured integration into the curriculum and continuous support. Nevertheless, the findings highlight the potential of mindfulness practices as a valuable tool for supporting students' psychological well-being during adolescence, providing them with coping mechanisms for the pressures they face. Future recommendations include expanding the program to a broader student population and offering more regular mindfulness sessions to foster long-term benefits